Transferring learning from the formal classroom to the clinical practice: A reflection on the training of speech therapists in Chile - Torres, Felipe; Romero, Luis; Álvarez, Carlos (Revista Chilena de Fonoaudiología, 2018)
In this paper, we present some reflections on the process of learning-transfer from formal classrooms to clinical practices, and the challenges involved for the training of speech therapist in Chilean higher-education institutions. We begin by analyzing the three levels of the current educational system in Chile: the macrosystem (general educational model), the mesosystem (educational models assumed by each higher-education institution), and microsystem (curricula adopted at universities), in order to provide a reference framework. Subsequently, we describe the Teaching Model for Understanding, we present evidence of application in institutions of higher-education in Latin America and we reflect on the impact that the implementation of this model might have for the process of transfer of learning. Finally, we consider the scope of the proposal and the possible limitations in its execution.